Salicylic Acid Mediated Modulation of Maize Germination under Induced Drought Stress - Khan, Tanveer; Khan, Salman; Jawad, Muhammad; Arshad Ullah; Shah, Sharif Ullah; Naveed, Asim; Khan, Taj Yousaf (Indus Journal of Bioscience Research, 2025)
This study aimed to assess the effects of varying concentrations of salicylic acid (SA) on the morpho-agronomic traits of maize (Zea mays L.) under induced drought stress. The evaluated morphometric parameters included germination percentage, germination index, germination rate index, root length, shoot length, and leaf count. A factorial experiment was conducted using a completely randomized design (CRD) with three replications to determine the influence of SA on the germination percentage of maize under drought conditions. The maize cultivar ‘Afsan’ was subjected to controlled drought stress. The findings demonstrated significant variations among different SA treatments under drought stress imposed for 5 and 10 days. Drought-induced dehydration in maize leaves was associated with reduced shoot and root growth. However, SA application alleviated the detrimental effects of drought stress by enhancing root length, shoot length, and leaf number. The study concludes that foliar application of SA at a 2% concentration is a cost-effective and efficient strategy for mitigating drought stress in maize.